Hubungan Antara Pola Asuh Orang Tua Dengan Perilaku Sosial Pada Anak Usia Dini di PAUD Tunas Bangsa Kota Padang - Ajizah, Siti Nur; Ismaniar, Ismaniar (Universitas Negeri Padang, 2023)
The background of this study is the poor parenting practices of parents in PAUD Tunas Bangsa, Padang City, which are a result of the pupils' subpar social skills. (1) To gain a general understanding of parenting practices in PAUD Tunas Bangsa, Padang City. (2) Visit Tunas Bangsa PAUD Padang City for a general review of social behavior in young children. (3) examining at PAUD Tunad Bangsa in Padang City how parenting practices and social behavior in young children relate to one another.This study is a quantitative correlational study, with the objective of determining the relationship between the independent and dependent variables. 28 pupils made up the study's population. This study used simple random sampling as its method of sampling.